Dilly's Sacrifice - Goodwin, Rosie (London Corsair, 2015)
Dilly is devastated: with her husband unable to work and four children already at home, they cannot afford to feed their new-born baby. Heartbroken, she heads into the night to deliver her baby girl to the Farthing family at the big house. Having just lost their own daughter to measles, the Farthings adopt the baby and offer Dilly a lifeline: a job as a maid. This act of desperation will change the lives of both families irrevocably - and the onset of WWI even more so. Sons are taken, love is declared, hearts are broken and terrible acts are committed. Through it all, Dilly does everything she can to preserve her family. But when the chance for true love finally comes, will she choose family over her own happiness?.
Keywords: Social classes